A large multicentre analysis of CTGF −945 promoter polymorphism does not confirm association with systemic sclerosis susceptibility or phenotype. Issue 10 (3rd December 2008) - Rueda, B; Simeon, C; Hesselstrand, R; Herrick, A; Worthington, J; Ortego-Centeno, N; Riemekasten, G; Fonollosa, V; Vonk, M C; van den Hoogen, F H J; Sanchez-Román, J; Aguirre-Zamorano, M A; et al.
Abstract : Objective: To conduct a replication study to investigate whether the −945 CTGF genetic variant is associated with systemic sclerosis (SSc) susceptibility or specific SSc phenotype. Methods: The study population comprised 1180 patients with SSc and 1784 healthy controls from seven independent case–control sets of European ancestry (Spanish, French, Dutch, German, British, Swedish and North American). The −945 CTGF genetic variant was genotyped using a Taqman 5′ allelic discrimination assay. Results: An independent association study showed in all the case–control cohorts no association of the CTGF −945 polymorphism with SSc susceptibility. These findings were confirmed by a meta-analysis giving a pooled OR = 1.12 (95% CI 0.99 to 1.25), p = 0.06. Investigation of the possible contribution of the −945 CTGF genetic variant to SSc phenotype showed that stratification according to SSc subtypes (limited or diffuse), selective autoantibodies (anti-topoisomerase I or anticentromere) or pulmonary involvement reached no statistically significant skewing. Conclusion: The results do not confirm previous findings and suggest that the CTGF −945 promoter polymorphism does not play a major role in SSc susceptibility or clinical phenotype.